Communicative interaction patterns of compliment giving and receiving among Iliganons - Garcia, Araceli Suico 1935-
This study was conducted to establish the use of compliments in the verbal and non-verbal interactions of Iliganon administrators, teachers, students, parents and their children, and friends. A questionnaire and a tape recorded observation were used as primary sources of data. It was revealed that the declarative, exclamatory and interrogative compliments are the most common forms of compliments used by the Iliganons. Based on the findings, the Iliganons are a happy, contented and inspired people.